An investigation of patent-intensive industries and government development strategy: evidence from China - Xuhua Chang; Nan Jiang; Hairui Liu (Asia Pacific Journal of Innovation and Entrepreneurship, 2022)
Purpose – The number of patents in China has grown rapidly in recent years. The purpose of this paper is to investigate how patents impact economic development in China. Design/methodology/approach – This paper developed an empirical model by using panel data of 42 China's patent-intensive industries to investigate the economic contribution made by Chinese patent-intensive manufacturing industries. Findings – This paper found that the intensity of valid patents is strongly positively related to economic growth. The intensity of yearly added patents presented an inverse U-shaped and a U-shaped curve with the economy made by China’s patent-intensive industries. The correlativity mainly depended on whether the patent intensity converges near the economic indicators. Meanwhile, from the perspective of input–output efficiency, for China’s patent-intensive industries, R&D institutes were overinvested, followed by R&D intensity and R&D staff. Originality/value – Investigating patent influence on economic development is quite complex research. Existing studies have mainly focused on patent protection in legal systems, but have not provided a definitive answer to what the real influence is. This study sought to narrow this gap from the patent economy perspective.